A conceptual framework for multi-way integration (MUWI) with a focus on residents’ multiple identities and intersectionalities - Schneider, Claudia (Dve domovini, 2025)
Conceptual frameworks on integration have moved from one to two-way integration, focusing on all residents in integration processes. This paper advocates a conceptual framework for “multi-way integration” (MUWI), which focuses explicitly on residents’ multiple identities and intersectionality to enhance connectivity and mutual understanding between all residents. The discussion also addresses factors impacting this connectivity, including social structures, social mechanisms, artifacts, and environments. The above dimensions and interconnections are not only relevant for researching integration processes but also for developing effective integration strategies.
Keywords: connectivity; migracije; migration; multy-way integration; povezanost; social mechanisms; socialni mehanizmi; večsmerna integracija